2023
DOI: 10.1002/agt2.373
|View full text |Cite
|
Sign up to set email alerts
|

Emission or scattering? Discriminating the origin of responsiveness in AIEgen‐doped smart polymers using the TPE dye

Abstract: Aggregation‐induced emission (AIE) luminogens are attractive dyes to probe polymer properties that depend on changes in chain mobility and free volume. When embedded in polymers the restriction of intramolecular motion (RIM) can lead to their photoluminescence quantum yield (PLQY) strong enhancement if local microviscosity increases (lowering of chain mobility and free volume). Nonetheless, measuring PLQY during stimuli, i.e. heat or mechanical stress, is technically challenging; thus, emission intensity is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[14][15][16][17] Nanoparticles of different sizes can be easily obtained by adjusting the bis-UPy concentration in the precursor solution; (ii) aggregation-induced emission (AIE) features of TPE derivatives eliminate the ACQ effect in FNPs, rendering fluorescence signals highly bright. [18][19][20][21][22][23] On this basis, a logarithmic correlation between the fluorescence intensity and nanoparticle size is successfully established for nanoparticles of TPE-UPy, TPEPy-UPy, and TPEDC-UPy with a correlation coefficient higher than 0.96. Theoretical calculations demonstrate that the bis-UPys at the surface and within the interior of the nanoparticles have different molecular pack-ing environments, which greatly influence the nonradiative decay rates of the TPE derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Nanoparticles of different sizes can be easily obtained by adjusting the bis-UPy concentration in the precursor solution; (ii) aggregation-induced emission (AIE) features of TPE derivatives eliminate the ACQ effect in FNPs, rendering fluorescence signals highly bright. [18][19][20][21][22][23] On this basis, a logarithmic correlation between the fluorescence intensity and nanoparticle size is successfully established for nanoparticles of TPE-UPy, TPEPy-UPy, and TPEDC-UPy with a correlation coefficient higher than 0.96. Theoretical calculations demonstrate that the bis-UPys at the surface and within the interior of the nanoparticles have different molecular pack-ing environments, which greatly influence the nonradiative decay rates of the TPE derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The photoluminescence properties of the system were also investigated. Obviously, a typical aggregation-induced luminescence can be observed as the system is subjected to UV irradiation (Figure a). , The PTO-1.5 hydrogel was injected into a mold and subsequently subjected to freeze–thawing to form the “FZU” shape. In addition, the as-prepared hydrogel (with a thickness of ∼1 mm) possessed adequate transmissivity (∼80%) in most visible light ranges (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…In the PVA film with 20% glycerol loading, the fluorescence gradient along the thickness direction can hardly be observed in the cross section. The recent work by Gualandi et al suggested a probability that light scattering will change the emission intensity of AIE luminogens during some common conditions like heating/cooling, stretching deformation, and physical aging, accompanied by polymer matrix transparency deterioration. However, the volatilizing PVA solutions as well as ultimately obtained films possessed high optical transparency, i.e., the transmittance within the visible-light range 400–800 nm preserved high as 90%.…”
Section: Resultsmentioning
confidence: 99%
“…In the PVA film with 20% glycerol loading, the fluorescence gradient along the thickness direction can hardly be observed in the cross section. The recent work by Gualandi et al 35 suggested a probability that light scattering will change the emission intensity of AIE During the evaporation of water, the mean concentrations of PVA in solutions (C m ) could be attained by a gravimetric analysis method. The slopes of MFI−thickness curves for both the skin layer and the core layer are plotted against C m , and the results are shown in Figures 2a and S3.…”
Section: Resultsmentioning
confidence: 99%